Ekstrak Cikal Tulang (Cissus quadrangularis) sebagai Alternatif Pencegahan Obesitas secara in Vivo: 29 - 34 - Surya, Maria Angeline Ivana; Chandra, Magdalena Leony; Nathaniela, Jocelin; Dewi, Ni Wayan Sucindra (Faculty of Medicine, Universitas Andalas, 2025)
Cikal Tulang (Cissus quadrangularis) contains ketosteroids that can be used as a traditional obesity treatment. Objective: To evaluated the potential of Cikal Tulang (Cissus quadrangularis) extract in preventing obesity (loss of body weight and abdominal fat) in Galur Swiss mice. Methods: A quasi-experimental post-test only design was conducted from July to August 2021, involving 30 male Swiss albino mice aged 1.5 months with body weights of 18–30 grams. The mice were divided into five groups: negative control (high-fat diet and fructose solution), positive control (orlistat 15.6 mg/kgBW), and three treatment groups receiving Cissus quadrangularis extract at doses of 30, 90, and 180 mg/kgBW for 14 days. The extract was administered orally via a gastric sonde. Body weight and Lee index were obesity parameters, and abdominal adipose tissue was analyzed morphometrically using hematoxylin-eosin staining. Data were analyzed with One-Way ANOVA at a significance level of p < 0.05. Results: One-Way ANOVA test showed significant differences in Lee index among groups before treatment (p = 0.0097), with values >300 indicating obesity. Post-treatment, Lee index decreased across groups but without statistically significant differences (p = 0.878), with values remaining >300. Conclusion: There was no significant association between administering cikal tulang (Cissus quadrangularis) extract and its anti-obesity effect. Keywords: anti-obesitas, cikal tulang (Cissus quadrangularis), fat